Incorporating Senior High School Students’ Responses Toward the Implementation of Group Investigation (GI) in Reading Narrative Text - Amelia, Nabilla; Mobit, Mobit; Puspitaloka, Nina (FKIP - Universitas Riau, 2024)
Students' response to reading long texts has an impact on their understanding of the main idea of the text due to the use of uninteresting teaching and learning techniques. This study aims to investigate how the Group Investigation (GI) is implemented in reading instruction, as well as to investigate students' responses to the GI in reading instruction. Qualitative method was used to conduct this research. Data were obtained from observation, interview, and documentation. This research uses a qualitative design and case study. Researchers conducted observations, semi- structured interviews, and documentation to collect data. The data analysis used in this research was conducted thematic analysis. The results showed that the incorporation of the group investigation have positive impact to students reading competency. In addition, students gave positive responses to the implementation of GI. Based on the interview results, students felt more motivated, involved, and enjoyed in the reading classroom practice. Thus, GI is a good alternative for classroom reading practice and the its incorporation in the classroom helps students' get comprehended reading material and the classroom environment become more active and fun.